A Case of Severe Seronegative Inflammatory Arthritis due to Nivolumab and Review of the Literature. (3rd November 2019) - Thapa, Bicky; Ali, Asad; Nair, Raunak; Vashisht, Rishik; Calabrese, Cassandra
Abstract : Immune-checkpoint inhibitors (ICIs) have revolutionized the treatment of cancer, yet therapy is often hampered by immune-related adverse events (irAEs) which range from mild to severe life-threatening events. Musculoskeletal (MSK) irAEs leading to discontinuation of ICIs are uncommon but increasingly recognized. We report a challenging case of severe immune-related seronegative inflammatory arthritis due to nivolumab in a patient with stage IV metastatic adenocarcinoma.